2021
DOI: 10.1038/s41598-021-91072-y
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for the diagnosis and post-Kasai portoenterostomy prognosis of biliary atresia: a systematic review and meta-analysis

Abstract: To evaluate the accuracy of biomarkers for the early diagnosis of biliary atresia (BA) and prognostic stratification after Kasai portoenterostomy (KPE). We conducted a systematic review of PubMed, Web of Science, Embase, Scopus and OVID for English literature reporting BA biomarkers published before August 2020. Screening, data extraction, and quality assessment were performed in duplicate. A total of 51 eligible studies were included in the systematic review, and data from 12 (4182 subjects) were extracted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 81 publications
3
23
0
Order By: Relevance
“…MMP7 was recently identified as a biomarker with promising potential, in particular as MMP7 levels can be established from a blood test [95] . A recently published meta-analysis has reported high sensitivity and specificity for the use of MMP7 in differentiating BA from other cholestatic diseases in newborns [99] . Genetic mutations can also be identified from DNA acquired through blood tests, but while genes with specific mutations (PKD1L1) [5] or carrying common variants in BA patients, such as ADD3, CRIPTO, NODAL, LEFTY, GPC, EFEMP1, ARF6, PCNT, KIF3B and TTC17 [ [6] , [7] , [8] , 11 ], continue to be identified, genetic screening will likely only capture a small percentage of BA patients, as most cases are nonsyndromic.…”
Section: Emerging Diagnostic Opportunities For Biliary Atresiamentioning
confidence: 99%
“…MMP7 was recently identified as a biomarker with promising potential, in particular as MMP7 levels can be established from a blood test [95] . A recently published meta-analysis has reported high sensitivity and specificity for the use of MMP7 in differentiating BA from other cholestatic diseases in newborns [99] . Genetic mutations can also be identified from DNA acquired through blood tests, but while genes with specific mutations (PKD1L1) [5] or carrying common variants in BA patients, such as ADD3, CRIPTO, NODAL, LEFTY, GPC, EFEMP1, ARF6, PCNT, KIF3B and TTC17 [ [6] , [7] , [8] , 11 ], continue to be identified, genetic screening will likely only capture a small percentage of BA patients, as most cases are nonsyndromic.…”
Section: Emerging Diagnostic Opportunities For Biliary Atresiamentioning
confidence: 99%
“…With universal newborn screening and increased availability of genetic testing, the majority of metabolic and genetic etiologies of neonatal cholestasis can be diagnosed in early infancy without a liver biopsy. For biliary atresia, a recent systematic review of biomarkers of disease showed a correlative value of high GGT with biliary atresia, surpassed only by a high serum MMP‐7 5 . However, the discriminatory value of serum MMP‐7 has not yet been validated in US cohorts.…”
Section: Case 3: Inconclusive Ancillary Evaluation and Liver Biopsymentioning
confidence: 99%
“…With emerging novel medical therapies for pediatric cholestatic disorders including BA 11 , 12 , understanding the pathophysiology of BA liver injury and how it relates to PE outcomes has become increasingly important 4 . As PE outcomes in individual patients remain highly variable, identification of accurate prognostic biomarkers reflecting the underlying key mechanisms driving liver injury would expedite targeted medical therapy, timing of LT and patient counseling 13 , 14 . In this respect, ductular reaction (DR), the histopathological hallmark of cholestatic disorders including BA, has been increasingly viewed as a potential therapeutic target for preventing progressive liver fibrosis 15 .…”
Section: Introductionmentioning
confidence: 99%